The longıtudınal evolutıon of covıd-19 outcomes among hemodıalysıs patıents: a natıonwıde multıcentre controlled study - TUĞCU, MURAT (My University, 2022)
Background: Hemodialysis (HD) patients have increased risk for short-term adverse outcomes of COVID-19. However, complications and survival at the post-COVID-19 period have not been published extensively. Methods: We conducted a national, multicenter observational study that included adult maintenance HD patients recovered from confirmed COVID-19. A control HD group without COVID-19 was selected from patients in the same center. We investigated the characteristics and outcomes in the follow-up of HD patients and compare them with the non-COVID group. Results: A total of 1223 patients (635 patients in COVID-19 group, 588 patients in non-COVID group) from 47 centers were included in the study. The patients' baseline and HD characteristics were almost similar. 28th day mortality and mortality between 28th day-90th day were higher in the COVID-19 group than non-COVID group [19 (3.0%) patients vs. none (0%); 15 (2.4%) patients vs. 4 (0.7%) patients, respectively]. The presence of respiratory symptoms, rehospitalization, need for home oxygen therapy, lower respiratory tract infection, A-V fistula thrombosis were significantly higher in the COVID-19 group in both the first 28 days and between 28-90 days. In the multivariable analysis, age [Odds ratio (OR) (95% confidence interval[CI]): 1.029(1.004-1.056)], group (COVID-19 group vs. non-COVID group) [OR (95%CI): 7.258(2.538-20.751) and vascular access type (tunneled catheter/AV fistula) [OR(95%CI): 2.512 (1.249-5.051)] were found as independent parameters related to 90-day mortality. Conclusion: In the post-COVID period, maintenance HD patients who have had COVID-19 have increased rehospitalization, respiratory problems, vascular access problems, and high mortality compared to the non-COVID HD patients.
Keywords: COVID-19; hemodialysis; nationwide study; outcome